Coulomb interaction effects in many-particle nuclear reactions with two-fragment resonance formation - A. V. Mikhailov; Yu. N. Pavlenko; V. L. Shablov; A. V. Stepaniuk; I. A. Tyras (Ядерна фізика та енергетика)
The modified final-state interaction theory taking into consideration the Coulomb interaction between two-fragment nuclear resonance decay products and accompanying reaction products is developed including the case of near-threshold resonances. The branching ratio change is also studied for the near-threshold resonance 7Li*(Ex = 7.45 MeV), which is formed in the reaction 7Li(α, α)7Li* at Eα = 27.2 MeV.